Management practices and challenges of holistic integrative health and nutrition services in early childhood education institutions: A qualitative study in Jember Regency, Indonesia - Nisa, Novia Izzatun; Yuniarta Syarifatul Umami; Laily Nur Aisiyah; Anggun Puspita Rini (Universitas Nahdlatul Ulama Surabaya, 2025)
Management is a structured and planned process conducted through several stages to achieve predetermined goals and objectives. Health and nutrition services are defined as efforts provided by schools or health-related organizations to optimize early childhood development. Holistic Integrative (HI) activities are government-initiated programs designed to stimulate key aspects of early childhood development through collaboration with schools, parents, and relevant institutions or agencies. Holistic integrated health and nutrition service management consists of planning, organizing, implementing, and supervising the HI process. This research was conducted in Kaliwates District, Jember Regency, specifically at Rukun Harapan Kindergarten and PGRI Kebon Agung Kindergarten, utilizing a descriptive qualitative method. The data collection process involved interviews, observation, and documentation. This study aims to analyze and elucidate holistic integrative health and nutrition service management practices suitable for kindergarten institutions. Furthermore, the findings may help the local government make informed policy decisions and provide foundational considerations for the development of holistic integrative health and nutrition service management concepts. The results demonstrate that both institutions engage in planning for health and nutrition services, including scheduling, operational budgeting, allocation of human resources, provision of supporting resources, and organizational management related to the division of health and nutrition service tasks. Additionally, the study identifies aspects of implementation and supervision management, as well as obstacles encountered in delivering holistic health and nutrition services in both institutions. In conclusion, several aspects can be optimized since they are not in line with the rules set by the government regarding early childhood education (PAUD) in kindergarten.